Determination of Rainfall Thresholds as Flood Triggers in the Klopogowok Watershed, Jember - Qatrinnada, Winona Fritzie Putri; Hidayah, Entin; Halik, Gusfan (Fakultas Teknik, Universitas Brawijaya, 2025)
The Klopogowok Watershed in Bangsalsari District, Jember Regency, often experiences flooding, which disrupts community activities and causes quite severe traffic congestion. This study aims to determine the rainfall threshold that triggers flooding using empirical methods to provide early warning and more effective mitigation measures. The data used in this study include rainfall data from the Global Precipitation Measurement (GPM) satellite and local observation data from 2014 to 2023. The approach used is consistency and correlation analysis between satellite and observation data. The analysis results show that flooding in the Klopogowok Watershed occurs with rainfall intensity ranging from 45 to 145 mm, lasting 6 to 19 hours. The empirical model obtained is I = 17.727D0.4858. This model has been proven to predict flood events, with the intensity-duration (I–D) equation able to identify the rainfall threshold that causes flooding quite well, with a coefficient of determination (R2) value of 0.732. Model validation using flood event data shows that this model can be used to provide early warning of potential flooding as a preventive measure. With integration into a real-time weather monitoring system, this model can be used as a basis for early warning of flooding in the Klopogowok Watershed. These findings will help policymakers in disaster mitigation, more effective water management planning, and improve community preparedness for flood disasters.